Direct democracy in high school: An experiment from Greece - Sykas, Theodosios; Peonidis, Filimon (JSSE - Journal of Social Science Education, 2022)
Keywords: School Community Assembly (SCA), direct democracy, school democratic governance Highlights: Only 5% of Greek secondary education students are satisfied with the modus operandi of student communities and councils. 5% of Greek adolescents are not interested in politics. The School Community Assembly (SCA) is a new decision-making and deliberative institution in which all high school students and all faculty members participate under conditions of equality. SCA promotes student’s direct participation in democratic decision-making and democratic school governance. SCA serves educational goals such as making students more considerate and public-spirited, more respectful of others and more responsible concerning their relation with the school community. Purpose: We discuss and preliminarily evaluate the SCA, a novel educational experiment that takes place in a Greek high school. Drawing on contemporary educational and political theory as well as the rich history of democratic ideas SCA has a twofold aim: to enable students to substantially participate in direct democratic decision-making procedures and to engage them along with their teachers in democratic school governance. Design/methodology/approach: SCA operates under conditions of democratic equality and mutual respect, since all students and teachers have one vote and the same speech rights, and its decisions are binding for the school community. The preliminary results that SCA has yielded so far, are based on the systematic observation of the SCA proceedings and a structured self-report questionnaire for students. Findings: SCA promotes democratic school governance, improves the school’s social climate, contributes to the development of certain democratic attitudes and skills, and helps students to become more responsible and public-spirited citizens.